Sun exposure among young people - Przybylska, Daria; Konopelko, Michał; Przybylski, Piotr; Szafraniec, Aneta; Porada, Dominik (Journal of Education, Health and Sport, 2018)
We are exposed to ultraviolet radiation every day. The amount of absorbed dose depends on the latitude, time of day, season of the year and the content of melanin in the skin. Deficiencies are the cause of many health problems and deterioration of the course of many disease processes. Negative effects on the cardiovascular system, on the formation of tumors or on the development of autoimmune diseases have been confirmed. In daily consumed foods, the dose of vitamin D is about 10% of the daily requirement. Increased physical activity, sunbathing when using radiation protection and oral supplementation allow you to achieve your goals. The level of vitamin D should be monitored regularly. There was a significant deficiency of vitamin D among athletes regardless of the type of sport performed. In addition to the benefits of sun exposure, we also get the risk of developing skin cancer. Risky behavior in the sun, the occurrence of erythema can contribute to the future of serious skin problems associated with cancer. We can prevent them by applying prophylaxis and individually selected sun protection. Education of patients, parents with small children families of patients with diagnosed melanoma and people with skin cancer may have positive effects in the future. Smoking and drinking alcohol have an adverse effect on sunbathing and the risk of sunburn. Planning for a pro-health policy should be based on preventive and public education programs. The increase in skin cancer cases around the world is alarming.